Medição de impedância utilizando sistemas digitais - Karla da Costa Ribeiro (2007)
Conducting measurements is, in the most part of practical situations, essential for scientific research. It is so important, that it can be said, that all areas in engineering are dependent of it. As well known, impedance measurement is a subject of great interest in many application fields, each of which has different demands in terms of accuracy, range,measurement rate and so on. In order to satisfy these needs and using different techniques, several circuits and instruments have been developed during the last years. This work presents an impedance meter which is capable of operating in real time and monitoring the system fundamental frequency and the unknown impedance without disconnecting the impedance from the circuit. These measurements can be done by acquiring the voltage and current signal of the unknown impedance followed by proper processing which is based onapplying discrete time domain techniques like digital filtering, downsampling and the discrete time Hilbert Transform. The developed measurement algorithm was called Complex Impedance Measurement Algorithm CIMA and its robustness was tested and validated computationally through the addition of electrical noise in the voltage and current signals. Experimental tests were performed and the results were compared with the values provided by commercial instruments (a RLC bridge of 0,2% accuracy and a 6,5 digits multimeter). Percent deviations are used to qualify the results and 8 impedances were measured: 3 resistors, 3 capacitors and 2 RC associations. In a complementary test, 3capacitors were initially measured and 2 of them were retired from the circuit using manual switching during the experiment. This was done in order to evaluate the measurement system capacity in detecting impedance variation and also to evaluate its settling time.